2020
DOI: 10.3390/foods9111568
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Diversity of Non-Korean Kimchi as Revealed by Viable Counting and Metataxonomic Sequencing

Abstract: Kimchi is recognized worldwide as the flagship food of Korea. To date, most of the currently available microbiological studies on kimchi deal with Korean manufactures. Moreover, there is a lack of knowledge on the occurrence of eumycetes in kimchi. Given these premises, the present study was aimed at investigating the bacterial and fungal dynamics occurring during the natural fermentation of an artisan non-Korean kimchi manufacture. Lactic acid bacteria were dominant, while Enterobacteriaceae, Pseudomonadaceae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
(81 reference statements)
2
11
0
Order By: Relevance
“…However, previous studies have reported significant changes to the microbial profile of kimchi during the fermentation process (Maoloni et al, 2020). Even though not statistically significant, the mean relative abundance of Firmicutes increased over 3 months of storage before starting to decline.…”
Section: Discussionmentioning
confidence: 67%
“…However, previous studies have reported significant changes to the microbial profile of kimchi during the fermentation process (Maoloni et al, 2020). Even though not statistically significant, the mean relative abundance of Firmicutes increased over 3 months of storage before starting to decline.…”
Section: Discussionmentioning
confidence: 67%
“…Further, if the UMB community was not separated via TFF, Cellulomonas biazotea and TM7a would not have been confirmed in kimchi. Available literature on kimchi microbial community analysis was reviewed, which led to the conclusion that Cellulomonas biazotea and TM7a have not yet been reported in kimchi via neither culture-dependent nor culture-independent methods (Cho et al, 2006; Jung et al, 2014; H.-W. Lee et al, 2017; Maoloni et al, 2020; E. J.…”
Section: Discussionmentioning
confidence: 99%
“…This pH value was related to the presence of lactic and nitric acids [ 50 ]. Other authors have shown a decrease in pH from a value of 5.0–5.4 at the beginning of fermentation of kimchi to 4.0 after 57 days of fermentation [ 51 ]. In turn, the pH value during fermentation of pineapple increased from 3.4 to 4.0 for fruits fermented by W. cibaria and to 3.5 for those fermented by Ln.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Changes in the microbial community during fermentation of plant products may additionally be caused by the production of antibiotics by microorganisms, including bacteriocins, which inhibit the growth of harmful bacteria [ 50 ]. Microbial analysis of kimchi carried out by Maoloni et al revealed formation of an active microbial community consisting predominantly of mesophilic aerobes and lactic acid bacteria [ 51 ]. The study showed that the total number of these bacteria in the product after nine days of fermentation reached >8 log10 CFU/g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation